Technical-environmental-economic evaluation of biomass-based hybrid power system with energy storage for rural electrification - Demirci, Alpaslan; Akar, Onur; Ozturk, Zafer (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
In recent years, higher penetrations of renewable energy generations helped persuade sustainable energy and environmental targets, although their intermittent and fluctuated nature raised technical challenges. However, hybrid power system can minimize these technical issues by integrating flexible generation capable renewable energy sources like biomass. This study deals with optimizing gridintegrated and stand-alone biomass-based hybrid power system for the energy demand of a rural region containing poultry farms. Besides solar and wind energy, energy storage integration is evaluated regarding overall technical-environmental-economic performance, considering the actual manure potential using HOMER Pro. In addition, sensitivity analyses are performed, considering the estimated load and inflations using an artificial neural network method. Using biomass and solar hybrid options offers more autonomous, environmentally friendly, and economic advantages. Biomass-based hybrid power system with solar energy reduced net present cost by around 12% and increased renewable fraction by 7%, and grid-connected options can provide 88.9% renewable fraction. In addition, the energy storage integration increased renewable fraction by around 10% and reduced excess energy by 16%. The proposed biomass-based hybrid power system achieves cost-effective sizing of solar or wind-based hybrid systems, empowers the reliability of renewable energy and presents good consistency of decarbonization targets.
Keywords: Anaerobic digestion; Animal waste; Biomass; CO 2 emission; Hybrid power system; Industrial livestock farms; PV-BIOMASS; DIESEL-BATTERY; PHOTOVOLTAIC-BIOMASS; BIOGAS PRODUCTION; SOLAR PV; FEASIBILITY; OPTIMIZATION; GENERATION; WIND; SENSITIVITY; Science & Technology - Other Topics; Energy & Fuels